Complementary Wet Cupping Therapy in Lowering Blood Pressure in Hypertension Patients - Suryadi, Moh.; Sholehah, Baitus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
More than 90 mmHg, which often causes complications in other body organs and causes various other complaints depending on the severity. Hypertension has risk factors including age and gender. Objective: This study aims to analyze the relationship between complementary wet cupping therapy and blood pressure in hypertensive patients. Method: The method in this research is an experimental research method with a pre-experiment design in a one group pretest posttest structure, data processing using SPSS Version 16.0 and statistical analysis using Wilcoxon Results: Research of 20 patients before carrying out wet cupping therapy, the degree of hypertension was found to be 15% pre-hypertension, 70% stage 1 and 15% stage 2. Meanwhile, after carrying out wet cupping therapy, it was found to be 65% pre-hypertension and 35% stage 1. Wilcoxon test results were obtained. The Z value is -3606 with a P-value (Asym p.Sig 2 tailed) of 0.000 which is less than the research critical limit of 0.05 so that H1 is accepted and H0 is rejected. Conclusion: There is a relationship between the application of cupping therapy in reducing blood pressure in hypertensive patients in the Islamic boarding school hamlet, Pajarakan Kulon Village, Probolinggo Regency